Clinical impact of Bachmann's bundle pacing defined by electrocardiographic criteria on atrial arrhythmia outcomes . Issue 9 (19th March 2022) - Infeld, Margaret; Nicoli, Charles D; Meagher, Sean; Tompkins, Bradley J; Wayne, Shawn; Irvine, Benjamin; Betageri, Omkar; Habel, Nicole; Till, Sean; Lobel, Jennings; Meyer, Markus; Lustgarten, Daniel L
Abstract: Aims: Evaluate whether Bachmann's bundle pacing (BBp) defined by electrocardiographic (ECG) criteria is associated with less atrial fibrillation/tachycardia (AF/AT) compared with anatomically defined right atrial septal pacing (RASp) and right atrial appendage pacing (RAAp). Methods and results: This is a retrospective study comparing BBp with non-specific RASp and RAAp on new incidence, burden, and recurrence of AF/AT. We included patients who underwent atrial lead placement between 2006 and 2019 and received > 20% atrial pacing. BBp was defined by paced P-wave morphology and fluoroscopic lead position. Compared with RASp ( n = 107) and RAAp ( n = 108), AF/AT burden was lower in the BBp ( n = 134) group by repeated measures ANOVA ( P < 0.001). Over 2-year follow-up, AF/AT burden increased in the RASp ( P < 0.01) and RAAp ( P < 0.01) groups but did not significantly change in the BBp group ( P = 0.91). Atrial arrhythmia burden was lower in the BBp group than the RASp and RAAp groups at 12–15, 18–21, and 24–27 months ( P < 0.05) after pacemaker placement. Risk of AF/AT recurrence was lower in BBp than RASp (HR 0.43; P < 0.01) and RAAp patients (HR 0.29, P < 0.01). Risk of de novo AF/AT was also lower in BBp than in RASp (OR 0.12; P < 0.01) and RAAp patients (OR 0.20, P < 0.01). Conclusion: Bachmann's bundle pacing defined using P-wave criteria was associated with decreased atrial arrhythmia burden, recurrence, and de novo incidence compared with right atrial septal pacing and right atrial appendage pacing.